(untitled) (Vietnam Journal of Community Medicine, 2026)
Reproductive health care for adolescents (CSSKVTN) is not only the task of the health sector but also requires the whole society. In which, parents, teachers, doctors, youth union, social organizations... must be the main subjects, actively cooperating in sex education programs.Adolescents often lack knowledge about sex, contraception, how to conceive, signs of pregnancy, sexually transmitted infections. Therefore, the study on awareness, attitude, and behavior about reproductive health for students of Nguyen Viet Xuan Secondary School, Ha Long City, has the following results: The rate of students with correct knowledge about pregnancy and the time when sexual intercourse is likely to cause pregnancy: mid-cycle 81.2%; Students’ knowledge about contraception; Students’ understanding of the harmful effects of abortion; STDs; Attitudes about reproductive health care for adolescents. Due to lack of knowledge about safe sex and reproductive health care (SRHC), many adolescents have suffered serious complications from unsafe abortion. Adolescent reproductive health care will guide them to think, evaluate, and make the right choices in friendship and love, not making regrettable mistakes that affect their happiness and future. Keywords: Family planning; Contraceptive measures; Current status of use, related factors when using contraceptive measures.